2021
DOI: 10.1111/ijcp.14145
|View full text |Cite
|
Sign up to set email alerts
|

Changes in liver fibrosis in patients with chronic hepatitis C after successful direct‐acting antiviral therapy

Abstract: Introduction and Objectives After successful treatment of hepatitis C virus (HCV) infection with direct‐acting antivirals (DAAs), the stage of liver fibrosis decreases over time. Here, we aimed to assess the changes in the liver fibrosis stage using transient elastography (TE) after successful DAA therapy in HCV‐infected cirrhotic patients who were referred to Shariati hospital from 2016 to 2017. Material and Methods In this observational cohort, all HCV‐infected cirrhotic patients who were treated with a comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 48 publications
1
10
0
2
Order By: Relevance
“…Theoretically, HCV eradication by DAA treatment is expected to regulate the expression of SREBP and reduce adipogenesis in the liver, which subsequently reduces CAP, an alternative marker of hepatic steatosis. Some previous studies have confirmed this conjecture [ 41 , 42 ]. However, recent reports have also shown that successful HCV eradication by DAA therapy may cause an elevation in CAP [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 66%
“…Theoretically, HCV eradication by DAA treatment is expected to regulate the expression of SREBP and reduce adipogenesis in the liver, which subsequently reduces CAP, an alternative marker of hepatic steatosis. Some previous studies have confirmed this conjecture [ 41 , 42 ]. However, recent reports have also shown that successful HCV eradication by DAA therapy may cause an elevation in CAP [ 43 , 44 ].…”
Section: Discussionsupporting
confidence: 66%
“…The factors that were associated with an increase in CAP values from the baseline to SVR are represented by impaired fasting glucose (fasting plasma glucose at baseline 106.37 ±18.86 mg/dL vs. 114.96 ± 47. 19 The patients with steatosis had higher LSMs (7.1 ± 1.5 kPa; SVR12-8.3 ± 3.8 kPa, p = 0.038), while patients without steatosis did not have higher LSMs (7.5 ± 1.4; SVR12 5.5 ± 1.2 kPa, p < 0.0001) (Table 2). Thus, 38.2% of the patients with steatosis had advanced fibrosis (F3), while patients without steatosis did not have advanced fibrosis (Figure 3…”
Section: Changes In Clinical and Biological Parametersmentioning
confidence: 92%
“…Several recent studies have found a significant regression of liver fibrosis after DAA treatment, but on the other hand, data from the literature are limited and contradictory regarding steatosis [19,20]. Hence, this study evaluated changes in liver steatosis using a CAP in patients with HCV infection who achieved SVR after 12 weeks of therapy completion.…”
Section: Introductionmentioning
confidence: 99%
“…В научной литературе данные о динамике стеатоза печени после достижения УВО противоречивы. Часть из них демонстрирует уменьшение САР ТМ по данным ТФ, в том числе и у пациентов с ЦП, через 12-24 недели после окончания терапии ПППД [32][33][34][35], другие, наоборот, прогрессию стеатоза печени [36][37][38]. В проведенном исследовании зарегистрирована высокая распространенность стеатоза печени как до начала ПВТ, так и при длительном мониторинге после достижения УВО.…”
Section: Discussionunclassified